Nudging for tax compliance: A meta-analysis - Armenak Antinyan; Zareh Asatryan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Taxpayer nudges - behavioral interventions that aim to increase tax compliance without changing the underlying economic incentives of taxpayers - are used increasingly by governments because of their potential cost-effectiveness in raising tax revenue. We collect about a thousand treatment effect estimates from over 40 randomized controlled trials, and in a meta-analytical framework show that non-deterrence nudges - interventions pointing to elements of individual tax morale - are on average ineffective in curbing tax evasion, while deterrence nudges - interventions emphasizing traditional determinants of compliance such as audit probabilities and penalty rates - are potent catalysts of compliance. These effects are, however, fairly small in magnitude. Deterrence nudges increase the probability of compliance by only 1.5-2.5 percentage points more than non-deterrence nudges, while the effects are likely to be bound to the short-run, and are somewhat inflated by selective reporting of results.
Keywords: C93; D91; H26; 330; Tax compliance; Randomized control trials; Nudging; Meta-analysis